PERAN PENAMBAHAN JUMLAH ENDORSER TERHADAP PERUBAHAN PERSEPSI RESPONDEN AKAN KEKUATAN IKLAN (suatu studi kasus pada media Audio) - Setiadi Umar; Agus Hasan Pura P.A (Center for Economic Studies Universitas Katolik Parahyangan, 2009)
In the advertising, a certain style of executing messages can be encountered based on testimonial evidence. As regards testimonial evidence, the marketing party involved can employ several endorsers or make use of only one in advertisements to deliver the message. The focus of study is on the extent to which messages' strength in term of attractiveness, convincingness, believability and persuasiveness can be altered by an increase in the number of endorsers. The research will test both messages that are perceived of having low quality persuasion and those are perceived of having high quality. The messages of the commercials are presented in audio-based commercials, a type of commercial that can only be heard by the respondents who cannot see the actual speaker's face.